2004
DOI: 10.1111/j.1365-2842.2004.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of PMMA resins containing γ‐methacryloxypropyltrimethoxysilane

Abstract: The polymethylmethacrylate (PMMA) resins containing c-methacryloxypropyltrimethoxysilane (c-MPS) of 0, 2, 4, 6, 10, 15, 20 and 30 mo1%, added to methylmethacrylate, were prepared using a monomer-polymer technique and stored in air or water at 37 % 0AE5°C for 28 days. The flexural strength and flexural modulus of the PMMA resins containing c-MPS of 20 and 30 mo1% were significantly smaller than those containing 2-6 mo1% and the same statements were true for the adhesive strength to porcelain tooth. However, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 11 publications
2
38
0
3
Order By: Relevance
“…The first one pertained to the degree of conversion of acrylic resin. Some studies reported that the Fs value decreased with increase in the content of other compounds added to acrylic resin 30,39) . In the context of the present study, the degree of conversion of acrylic resin might be adversely affected because of the addition of other material namely TiO2 or Ap-TiO2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one pertained to the degree of conversion of acrylic resin. Some studies reported that the Fs value decreased with increase in the content of other compounds added to acrylic resin 30,39) . In the context of the present study, the degree of conversion of acrylic resin might be adversely affected because of the addition of other material namely TiO2 or Ap-TiO2.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, adhesive monomers such as 4-methacryloxyethyl trimellitate anhydride (4-META) and -methacryloxypropyltrimethoxysilane ( -MPS) have been used to improve bonding between metal and resin [39][40][41] . In the context of the present study, the physical and mechanical properties of acrylic resin containing TiO2 or Ap-TiO2 might be impaired by adding an adhesive monomer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the amount of photocatalyst that was contained in the resin was the dominant factor in the reduction of mechanical strength. Kanie et al reported that when γ-methacryloxypropyltrimethoxysilane was added to PMMA resins to increase the adhesive strength to porcelain tooth, the flexural strength of the PMMA resins decreased 22) . They reported that this was due to inhibited polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction may explain the finding that increased silane coupling agent in PMMA resulted in more water absorption. 31 Moreover, the dissociation energy of the Si-O bond in the silane coupling agent is higher than that of Zn-O. 32 Therefore, unbound Zn ions that have an antifungal effect can easily dissociate due to water absorbing into the material.…”
mentioning
confidence: 99%